Eruption of Permanent Teeth in Bulgarian Children Aged 5–12 Years - Boyan Valentinov Kirilov; Ivaila Yankova Ivanova-Pandourska; Yanitsa Velichkova Zhecheva (Anthropological Review, 2025)
The time of eruption and the number of permanent teeth together with the time of sexual maturation and ossification of the skeleton are important indicators of the biological maturity and health of children. The aim is to evaluate the eruption of permanent teeth in Bulgarian children aged 5–12 years and to assess its relationship with age and sex. The present cross-sectional study included 709 individuals from 5 to 12 years. The oral and dental status was checked and included the number of erupted teeth (NET). Statistical analyses were performed to compare the sexes and ages. Statistically significant differences between sexes are observed only in teeth 17, 27, 33 and 43. The sequence of tooth eruption was examined, and it is almost identical in male and female subadults. Mandibular teeth erupt earlier than maxillary teeth, excluding first premolars for both sexes and canines in males. Females have earlier tooth eruption and more permanent teeth compared to males. A significant association between age and NET is established. Sex does not have a significant effect on tooth eruption. The time of eruption of permanent teeth is influenced significantly by age, but not by sex in our sample. Differences between males and females are found in the sequence of eruption only of canines and premolars. Females tend to have earlier tooth eruption and more erupted teeth. Lower teeth erupt earlier than upper teeth, excluding first premolars in both sexes and canines in males.